دابەشبوونی جوگرافیای كانزاكاری چەوولم لەقەزای شارباژێر و كاریگەری لەسەر گۆڕانی ڕووپۆشی زەوی (Land cover) بەبەكارهێنانی سیستمی زانیارییە جوگرافیەكان - عبدالرحمن, ڕۆژان فەرەیدون; سعید, دڵشاد محمد (Sulaimani Journal for Humanities, 2023)
This research is (Geographical distribution of mining gravel and sand in Sharbazher district and its impact on land cover changes using geographical information systems), because mining is one of the most important occupations that contributes to the economy and reconstruction of human civilization In the manufacture of cement solutions, therefore, the metallurgical factories in the study area are a basic necessity to supply the produced materials (gravel and sand and pebbles) to the market of the region and Sulaimani. This occupation creates many environmental problems and changes in the natural features of the region.The main objective of this study is to show the geographical distribution of mining factories and the changes as a result of the implementation of the industry on the land cover of the region during the years (2000-2020).